Effects of Urban Agriculture on the Socio-Economic Status of Farmers in Cities of Sub-Sahara Africa. A case of Zambia, South Africa, and Nigeria: A Review - Ninsheka, Leonard; Ssemakula, Edward; Tiyo, Christopher; Kalibwani, Rebecca; Kityo, Ronald; Mugizi, Wilson; Byamukama, Willbroad (East African Nature and Science Organization, 2024)
This paper reviews the current literature concerning the effect of urban agriculture on the socio-economic status of urban farmers in Sub-Sahara African Cities. The main objective of this review is to examine the impacts of urban agriculture on the socio-economic status of urban farmers in Sub-Sahara African Cities. Specifically, the paper reviews the impact of urban agriculture on income and food security as well as the benefits and challenges affecting urban Agriculture development in selected cities of sub-Saharan African countries. This paper reviews different articles and papers on urban farming in Sub-Sahara Africa and globally. The review posits that there is scanty information on how urban agriculture affects farmers' socio-economic status in sub-Saharan Africa. How farmers derive their social and economic status by engaging in urban agriculture, and the types and motivations of farmers are not clear. The review suggests that understanding the factors that are crucial for food security, income and related benefits in urban agriculture is essential to developing the right technologies and policies